2021
DOI: 10.3390/en14185723
|View full text |Cite
|
Sign up to set email alerts
|

FeI Intermediates in N2O2 Schiff Base Complexes: Effect of Electronic Character of the Ligand and of the Proton Donor on the Reactivity with Carbon Dioxide

Abstract: The characterization of competent intermediates of metal complexes, involved in catalytic transformations for the activation of small molecules, is an important target for mechanistic comprehension and catalyst design. Iron complexes deserve particular attention, due to the rich chemistry of iron that allows their application both in oxidation and reduction processes. In particular, iron complexes with tetradentate Schiff base ligands show the possibility to electrochemically generate FeI intermediates, capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Such a high selectivity has also been reported for [Fe III (L 1 )Cl] under electrocatalytic conditions. 22 Finally, Figures 2 and S14 also show that the addition of LiClO 4 has a remarkably stimulating effect on the activity of the catalyst. The initial rate slightly increased upon addition of LiClO 4 up to 500 μM, 20 equiv with respect to the catalyst, and then decreased upon further addition; the reaction proceeded with a constant rate for longer time to reach, with the addition of 500 μM LiClO 4 , a maximal TON CO value, after 120 min reaction, of 1532, indicating a stabilizing effect of the added salt.…”
Section: Ligands and Complexesmentioning
confidence: 87%
See 1 more Smart Citation
“…Such a high selectivity has also been reported for [Fe III (L 1 )Cl] under electrocatalytic conditions. 22 Finally, Figures 2 and S14 also show that the addition of LiClO 4 has a remarkably stimulating effect on the activity of the catalyst. The initial rate slightly increased upon addition of LiClO 4 up to 500 μM, 20 equiv with respect to the catalyst, and then decreased upon further addition; the reaction proceeded with a constant rate for longer time to reach, with the addition of 500 μM LiClO 4 , a maximal TON CO value, after 120 min reaction, of 1532, indicating a stabilizing effect of the added salt.…”
Section: Ligands and Complexesmentioning
confidence: 87%
“…19,20 Iron complexes based on Schiff-base N 2 O 2 -type ligand, N,N′bis(salicylaldehyde)-1,2-phenylenediamine (salophen), have been studied for the electrocatalytic reduction of CO 2 . 21,22 Surprisingly, no study has been reported on the catalytic properties of these Fe-salophen complexes for light-driven reduction of CO 2 , in spite of the fact that Fe is the most abundant transition metal on earth and, furthermore, this class of ligand allows a great synthetic versatility, offering opportunities to easily explore structure−activity relationships.…”
Section: Introductionmentioning
confidence: 99%
“…For both complexes 1 and 2, the "unpolished electrode" test performed after 2 h bulk electrolysis confirms that the observed catalysis is not due to heterogeneous species formed at the electrode surface. [26] Negligible currents, associated with only trace amounts of H 2 , were indeed measured upon electrolysis of a catalyst-free solution using a GC electrode previously employed for electrolysis tests with either 1 or 2.…”
Section: Electrocatalytic Co 2 Reductionmentioning
confidence: 99%
“…In this regard, molecular catalysts based on transition metal complexes have received considerable interest due to their great versatility and tunability over heterogeneous materials. Examples of this kind include rhenium and ruthenium complexes [7–16] as well as complexes of earth‐abundant metals, [17–44] whose activity mainly results in the generation of CO or formate (Eqs. (2), (3)).…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Gurpreet and coworkers investigated the activity of mono- and dinuclear complexes of Cr, Mn, Fe, Co, and Ni with macrocyclic Schiff base cuprolic ligand for catalytic CO 2 reduction, which could efficiently convert CO 2 to methane at a potential of −0.24 V [ 54 ]. In 2021, Bonetto et al studied the carbon dioxide reduction properties of five Fe(III) complexes of Schiff-base-containing donor sites N 2 O 2 , which show the overpotential of Fe(salen) of 910 mV, K cat of 50,000 s −1 [ 55 ]. Nevertheless, as yet, there has been no reported Schiff base complex acting as bifunctional electrochemical catalyst for CO 2 reduction and water oxidation.…”
Section: Introductionmentioning
confidence: 99%